2015
DOI: 10.1007/s13313-015-0380-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable segregating SSR markers for blast resistance in rice using inheritance and disease reaction analysis in backcross families

Abstract: The study was conducted to identify the suitable SSR markers in relation to blast disease of rice. Backcross breeding was applied and BC 2 F 1 generation was produced using rice variety Pongsu Seribu 2 as blast resistant parent and MR219 as susceptible parent. Eleven SSR markers related to blast resistance genes (Pi gene) were found highly polymorphic between the parental lines. According to single-gene model only two markers, RM208 and RM206, fitted to the expected test cross ratio (1:1) in BC 2 F 1 generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
6
5
0
Order By: Relevance
“…They were both located on chromosome 11 with 149 and 129 bp, respectively. These results agree with the findings by Tanweer et al (2015a), who identified the Pi-kh gene using RM206. Likewise, Hasan et al (2015) and Ashkani et al (2013) identified Pi-7(t) using RM5961 and PS2 as the donor parent.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They were both located on chromosome 11 with 149 and 129 bp, respectively. These results agree with the findings by Tanweer et al (2015a), who identified the Pi-kh gene using RM206. Likewise, Hasan et al (2015) and Ashkani et al (2013) identified Pi-7(t) using RM5961 and PS2 as the donor parent.…”
Section: Discussionsupporting
confidence: 92%
“…In Malaysia, inheritance studies have been performed using local isolates (Rahim et al, 2012), including BC 2 F 3 and BC 2 F 5 advanced backcrosses (Oryza rufipogon x MR219). Four dominant genes at different loci were identified against the most virulent pathotype of M. oryzae Tanweer et al, 2015a). In addition, Ashkani et al (2015) reported an epistatic effect in a study including two different races of fungus.…”
Section: Introductionmentioning
confidence: 97%
“…This Chi-square result obtained for blast resistance loci was in line with the result reported by Tanweer et al [54] who recorded foreground marker segregation ratio of 53:106:41 and 55:107:38 for RM208 and RM206 respectively which fitted into the 1:2:1 segregation ratio expected from Mendel studies. Also, Miah et al [15] reported a segregation ratio of 52:127:74 (RM8225) and 54:132:67 (RM6836) which did not differ significantly from the expected Mendelian ratio of 1:2:1.…”
Section: Discussionsupporting
confidence: 91%
“…More than 100 race specific blast resistance genes have been identified up to date in rice [6,7], and hundreds of quantitative trait loci (QTL) associated with blast resistance have been mapped [8]. Molecular markers linked to these genes and loci have been widely reported and used for assisted breeding of blast resistance [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%